ECOTOURISM DEVELOPMENT IN TANJUNG BALAI DISTRICT, NORTH SUMATERA: MANGROVE FOREST ECOLOGICAL FACTORS - Fahriansyah Fahriansyah; Dessy Yoswaty (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
District of Tanjungbalai characterized by mangrove ecosystem with mud and sandy beaches has the potential to be developed for marine ecotourism. One way to maintain the existence of mangrove forests from destruction or extinction is to develop the Tanjungbalai district to be an ecotourism area. The research objective was to determine the potential ecological mangrove forest to be developed as an ecotourism area. The study was conducted in August-November 2011, using survey methods. Primary data were obtained through direct observation in the village of Bagan Asahan, Asahan Mati and Sungai Apung on mangrove community structure (density value) and ecological potential. Data analyses for suitability tourism index were based on Yulianda (2007). The results showed that the mangrove forest in the Tanjungbalai District had a good density in the category of very dense (the value of 1778 ind./Ha), mainly consisting of Bruguiera gymnorrhiza, Xylocarpus granatum, Rhizophora mucronata and Rhizophora apiculata. Suitability tourism index in the Tanjungbalai District was very suitable (S1) for mangrove tourism development including Village of Bagan Asahan (score 65, IKW 85.53%), Asahan Mati (score 61, IKW 80.26%) and Asahan Apung (score of 61, IKW 80.26%). Ecologically, mangrove forests in the district of Tanjungbalai is potential to serve as a mangrove ecotourism area. Keywords: mangrove forest, potential ecological, ecotourism development